The significance of DOHaD for Small Island Developing States. (12th July 2018) - Tu'akoi, S.; Vickers, M. H.; Tairea, K.; Aung, Y. Y. M.; Tamarua-Herman, N.; 'Ofanoa, M.; Bay, J. L.
Abstract: Small Island Developing States (SIDS) are island nations that experience specific social, economic and environmental vulnerabilities associated with small populations, isolation and limited resources. Globally, SIDS exhibit exceptionally high rates of non-communicable disease (NCD) risk and incidence. Despite this, there is a lack of context-specific research within SIDS focused on life course approaches to NCD prevention, particularly the impact of the early-life environment on later disease risk as defined by the Developmental Origins of Health and Disease (DOHaD) framework. Given that globalization has contributed to significant nutritional transitions in these populations, the DOHaD paradigm is highly relevant. SIDS in the Pacific region have the highest rates of NCD risk and incidence globally. Transitions from traditional foods grown locally to reliance on importation of Western-style processed foods high in fat and sugar are common. The Cook Islands is one Pacific SIDS that reports this transition, alongside rising overweight/obesity rates, currently 91%/72%, in the adult population. However, research on early-life NCD prevention within this context, as in many low- and middle-income countries, is scarce. Although traditional research emphasizes the need for large sample sizes, this is rarely possible in the smaller SIDS. In these vulnerable, high priority countries, consideration should be given to utilizing 'small' sample sizes that encompass a high proportion of the total population. This may enable contextually relevant research, crucial to inform NCD prevention strategies that can contribute to improving health and well-being for these at-risk communities.